Burnout: solve your stress cycle - Nagoski, Emily; Nagoski Amelia (London: Vermilion, Ebury publishing, 2020)
Explores the unique stressors women face, particularly the societal expectations placed on them, and how these contribute to burnout. The book emphasizes the importance of completing the stress cycle, not just for physical health but also for emotional well-being, offering strategies like physical activity, social connection, and creative expression to help women manage stress and reclaim their lives.
Includes index
mnn & 10/06/25
Loans
Keywords: Nagoski and Amelia; Stress management; Burnout (Psychology); Mental health; Work-life balance; Women; Health and hygiene